Kedudukan Hukum Anak di Luar Perkawinan dalam Pembagian Waris Menurut KUHPerdata dan Perkembangannya dalam Yurisprudensi Mahkamah Agung - Bebly Rajes Punjabi (Jurnal Riset Multidisiplin Edukasi, 2025)
The legal status of children born outside of marriage in inheritance matters continues to create uncertainty, particularly because the Indonesian Civil Code (KUHPerdata) has not fully adapted to regulatory developments and the expanded scope of civil relations following Constitutional Court Decision No. 46/PUU-VIII/2010. This study aims to analyze the regulation of the inheritance rights of extramarital children under the KUHPerdata and to examine the implications of integrating biological evidence, the principle of child protection, and judicial law-making in court practice. This research employs a normative legal method with statutory, case, and conceptual approaches. The findings show that the Constitutional Court decision has broadened the civil relationship of extramarital children, influencing their inheritance position despite the formal restrictions that remain in the Civil Code. Moreover, biological testing such as DNA enhances the evidentiary certainty of blood relations, while the principle of child protection and judicial interpretation allow judges to adopt a more progressive view in inheritance cases. In conclusion, jurisprudential developments have shifted judicial practice toward a more equitable inheritance framework for extramarital children, although legislative reform remains essential to achieve comprehensive legal certainty.